A mobilidade da força de trabalho e do consumo nas feiras de Maringá (PR-BRASIL) e de Leiria (PORTUGAL) : a resistência do setor no contexto do capitalismo global - Bernardino, Virgílio Manuel Pereira (2015)
Currently, the fairs are surrounded by difficulties, threats, conflicts and doubts, characteristics of the globalization era, requiring skills of stallholders set out to overcome the difficulties. This study relied on human displacement (mobility resellers fairground, fairground and producers, plus consumer) to a node of urban space: the fair. These mobility of labor and consumption operate evidence of the effectiveness of counter-rationalities and parallel rationalities that arise as realities against the hegemonic capitalism, and indicate 'new' and unsuspected paths to thought and socioeconomic and cultural action of the Brazilian population and Portuguese. Therefore, the fairs are places, sites of resistance, spaces survival of solidarity happenings, real and effective possibilities for communication, information exchange and political integration; are counter-rationalities and constraints resistant to change in a globalized world; are differential spaces (LEFEBVRE) and points of networks. Thus, the aim of this study is to analyze the trade Producer of Maringa and Leiria mobilities of fairground workers and the extent of resistance of workers in the sector, compared to their future continuity in global capitalism. The results allowed us to represent / map the joints of different spaces conditioned by the mobility of the workforce and consumption of Maringa and Leiria birth culture and the meanings within. The concern with the urban mobility of the population and, in particular, the mobility of workers, is a significant issue for those who live in cities, and Leiria and Maringa is no different. The mobility and structure of society itself has been modified due to new crises of capitalism and the arising needs of a large portion of the population that is unemployed. We emphasize the role of the fair as specific dynamics, the result of accumulation of natural processes that have evolved from crises originating from different times (HARVEY). So the prospect of economic solidarity, popular cooperatives, consumption next, sustainable production and other alternative actions can be engendered in local economies, providing better answers to workers and consumers. It's in crisis that the possibility of change appears as an alternate path to a more just society.